Photosensitizer-Conjugated Human Serum Albumin Nanoparticles for Effective Photodynamic Therapy - Jeong, Hayoung; Huh, MyungSook; Lee, So Jin; Koo, Heebeom; Kwon, Ick Chan; Jeong, Seo Young; Kim, Kwangmeyung (IVYSPRING INT PUBL, 2011)
Photodynamic therapy (PDT) is an emerging theranostic modality for various cancers and diseases. The focus of this study was the development of tumor-targeting albumin nanoparticles containing photosensitizers for efficient PDT. To produce tumor-targeting albumin nanoparticles, the hydrophobic photosensitizer, chlorin e6 (Ce6), was chemically conjugated to human serum albumin (HSA). The conjugates formed self-assembled nanoparticle structures with an average diameter of 88 nm under aqueous conditions. As expected, the Ce6-conjugated HSA nanoparticles (Ce6-HSA-NPs) were nontoxic in their native state, but upon illumination with the appropriate wavelength of light, they produced singlet oxygen and damaged target tumor cells in a cell culture system. Importantly, when the nanoparticles were injected through the tail vein into tumor-bearing HT-29 mice, Ce6-HSA-NPs compared with free Ce6 revealed enhanced tumor-specific biodistribution and successful therapeutic results following laser irradiation. These results suggest that highly tumor-specific albumin nanoparticles have the potential to serve not only as efficient therapeutic agents, but also as photodynamic imaging (PDI) reagents in cancer treatment.